Economic development in South Asia - Khan, Mohsin S. (Tata McGraw-Hill, 2005)
Contributed articles on economic policy in South Asia presented at Fourth Annual SANEI Conference at Dhaka, in 2002 initiated by South Asia Network of Economic Research Institutes.